Vertical organic synapse expandable to 3D crossbar array - Yongsuk Choi; Seyong Oh; Chuan Qian; Jin-Hong Park; Jeong Ho Cho (Nature Communications, 2020)
Though three-terminal organic synapses are attractive for artificial neural networks due their weight controllable property, their structural limitations hinder performance. Here, the authors report a crossbar synapse array featuring vertical organic synapses with remote weight update capability.